INTERNET FORUM AS AN ENVIRONMENT OF PSYCHOLOGICAL SUPPORT OF MARRIED COUPLES FROM THE FAMILIES OF MIGRANT WORKERS IN A SITUATION OF FORCED SEPARATION - Валентина Васильевна Гриценко; Мария Николаевна Ефременкова (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
The purpose of this work is to describe the psychological characteristics of communication of forum members concerning the situation of forced separation of married couples in a situation of labor migration. Practical relevance and novelty of the work is to identify opportunities of the Internet environment for psychological support for  migrant workers’ families. Through the method of content analysis of materials of the Internet forums, the motives for applying for psychological support of family members  to the participants of virtual communication in the situations of labor migration are identified, the reactions of the forum members on the suggested topics are analyzed. It is noted that the actuality of applying to the Internet resources often occurs at the stage of  taking a decision of labor migration, rarely - at the stage of separation, as a rule, by the remaining partner. Most forum members assess a situation of going of one of the partners to work critically, describing negative scenarios. The article deals with coping strategies described on the forum which are estimated as the point of support, the expansion of psychological experience in a situation of forced separation. The examples of adaptive, not adaptive or relatively adaptive coping mechanisms implemented by the Forum members are given.  The final conclusion of the article is an overview of possibility of communication in the Internet forums to search for effective strategies for coping with the situation of forced separation due to migration. DOI: http://dx.doi.org/10.12731/2218-7405-2013-4-23